Dinamika Hara Gambut Pada Penggunaan Lahan Hutan Sekunder, Semak Dan Kebun Kelapa Sawit - Heru Bagus Pulunggono; Syaiful Anwar; Budi Mulyanto; Supiandi Sabiham (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Peat nutrient dynamics research was intended to study the characteristics and distribution of macro nutrients in peat water and peat in secondary forests, shrubs and oil palm plantations. This research was conducted with purposive sampling method. Observations on oil palm plantations were carried out at three ages of oil palm (5, 12, and 16 years). Secondary forest and shrub peatlands were used as a comparison. Sampling of peat water and peat was carried out during the rainy and dry season, at four distances from the collection drain (25, 50, 75, and 150 m). The results showed that nutrient levels in peat water during the dry season were greater than the wet season. The status of peat water and peat nutrients in secondary forests and shrubs is relatively the same as that of oil palm plantations that were fertilized. Seasonal, land use and distance from the collection channel differences did not have a major influence on the distribution and characteristics of macro nutrients on peat. The macro nutrients content of peat water and peat, however, showed an increase with the distance from the collection channel.